The Oxford handbook of the history of physics - Buchwald, Jed Z.; Fox, Robert, 1938- (Oxford : Oxford University Press, 2013)
This book brings together cutting-edge writing by more than twenty leading authorities on the history of physics from the seventeenth century to the present day. By presenting a wide diversity of studies in a single volume, it provides authoritative introductions to scholarly contributions that have tended to be dispersed in journals and books not easily accessible to the general reader. While the core thread remains the theories and experimental practices of physics, the Handbook contains chapters on other dimensions that have their place in any rounded history. These include the role of lecturing and textbooks in the communication of knowledge, the contribution of instrument-makers and instrument-making companies in providing for the needs of both research and lecture demonstrations, and the growing importance of the many interfaces between academic physics, industry, and the military. --
part. I. Physics and the new science -- part. II. The long eighteenth century -- part III. Fashioning the discipline : from natural philosophy to physics -- part IV. Modern physics.
Includes bibliographical references and indexes.
Keywords: Physics -- History; Science -- History